GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF BIOACTIVE COMPONENTS FROM THE RHIZOME EXTRACT OF NARDOSTACHYS JATAMANSI DC - ME, VEENA; P, NIRANJANA; N Achur, Rajeshwara (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT In this study, the bioactive compounds of Nardostachys jatamansi have been evaluated using gas chromatography-mass spectrometry (GC-MS). The chemical composition of the rhizome of N. jatamansi, petroleum ether, chloroform, and ethanol extract was investigated using agilent 7890 GC-MS instrument. N. jatamansi extract contains 61 compounds, i.e., actinidine (11.2%), indane (28.7%), aristolene (7.2%), gurjuenen (5.5%), valencene (8.9%), globulol (8.2%), betapatachoulene (8.4%), etc. Actinidine and indane are the major compounds in the ethanol extract along with few minor compounds. Keywords: Chloroform extract, Gas chromatography-mass spectrometry analysis, Nardostachys jatamansi.